The Effect of Chrysonilia crassa Additive on Duodenal & Caecal Morphology, Bacterial & Fungal Number, and Productivity of Ayam Kampung - Turrini Yudiarti; V. D. Yunianto B.I; R. Murwani; E. Kusdiyantini (International Journal of Science and Engineering, 2012)
Fungi is a microorganism that can live in gastrointestinal tract of chicken. One type of fungi is multicellular or filamentous fungi. C.crassa is a species of filamentous fungi that has been isolated in the earlier study and it showed the best probiotic potency in vitro. The obyective of this research was to study the effect of addition of dried culture of  C.crassa in feed on intestinal & caecal morphology, bacterial & fungal number, and  productivity of indigenous chicken (ayam kampung). Research used completely randomized design with four treatments. The treatments were the level of  dried culture in basal diet (0%, 0.25 %,  0.50 % and 0.75 %). Each treatment was replicated 5 times and each replicate consists of 10 chickens. The parameters observed were : villi morphology, number of bacteria and fungi in the duodenum and cecum of chickens aged 1, 21 and 35 days and productivity i.e. feed intake, final body weight and feed conversion. The results showed that 0.50% dried culture of C.crassa could increase the duodenal villi width, decreased the number of bacterial and fungal colonies in duodenum and caecum, but it did not increase productivity. The conclusion : C.crassa could stimulate the duodenal villi development and decreased the number of the bacteria and fungi in the gastrointestinal tract, yet it has no positive impact on the chicken productivity.